A cytogenetic study of the antimutagenic potential of herbal infusions from Matricaria chamomilla L. and Achillea millefolium L. (Fam. Asteraceae) (Experimental biology, 2020)
Due to increase of hazardous factors in the environment, it becomes relevant to search for effective protectors of natural origin for the correction of toxic and genetic effects induced by xenobiotics. Using the test for count chromosomal abnormalities in cells of root germinal meristem of barley seeds, the mutagenic and antimutagenic activity of infusions from chamomile (Matricaria chamomilla) and yarrow (Achillea millefolium) were studied. The studied infusions with various preparation methods (concentrated, diluted and phyto tea) did not show mutagenic activity. The frequency of structural mutations was at the level of negative control (distilled water). The ability of yarrow and chamomile infusions to reduce MMS-induced mutagenesis has been established. For direct and reverse treatment of seeds with diluted infusions or herbal tea of medicinal plants and mutagen methyl methanesulfonate (MMS, positive control) a statistically significant decrease of MMS-induced was observed (p